Review of the species of Macrodactylus Dejean (Coleoptera: Scarabaeidae: Melolonthinae) from Costa Rica and Panama - Arce-Pérez, Roberto; Morón, Miguel Ángel (Zootaxa, 2018)
Fifteen species of Macrodactylus Dejean (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini) from Costa Rica and Panama are described and illustrated, including eight new species: M. latreillei new species., M. pseudothoracicus new species. and M. dejeani new species from Costa Rica; M. solisi new species from Costa Rica and Panama; M. martinezi new species from Costa Rica and Venezuela; M. chiriquiensis new species and M. kunayalaensis new species from Panama; and M. moroni new species from Costa Rica, and Panama. Diagnosis for seven species previously recorded in Costa Rica and Panama are included, and a key to all known species of Macrodactylus in these countries is provided.